Impact of Plant Spacing and Fertilization Dose on the Growth and Yield Traits of Okra (Abelmoschus esculentus (L.) Moench) in Sudan - Abdalla, Ashraf Izzeldin; Mohammed, Einas Amar Salem; Mahdi, Mahdi Mohammed; Khiery, Nahid Tagelsir (Journal of Tropical Crop Science, 2024)
This study examines the impact of plant spacing and nitrogen fertilization doses on the growth and yield traits of okra (Abelmoschus esculentus (L.) Moench) in Sudan. Using a factorial experiment within a completely randomized block design, the research explored four spacing levels within raw, S1, S2, S3, and S4 (20, 25, 30, and 35 cm, respectively) and four nitrogen fertilizer doses, Ur1, Ur2, Ur3 and Ur4 (60, 80, 100, and 120 kg.ha-1 , respectively). Key metrics were measured: plant height, number of leaves, number of nodes, pod length, fresh weight, and seed count per pod. The results, analyzed via OPSTAT statistical software and ANOVA, indicated that a 60 cm × 30 cm spacing combined with a nitrogen dose of 60 kg.ha-1 significantly optimized growth parameters and yield components. Specifically, this combination resulted in the tallest plants (15.50 cm), the highest number of leaves (7.30), nodes (7.30), and greater fresh pod weight (7.69 g) and length (5.50 cm). Significant interaction effects between spacing and fertilizer doses were observed across all parameters at a 5% confidence level. The study recommends a 60 cm × 30 cm spacing with a nitrogen dose of 60 kg.ha-1 to maximize okra growth, yield, and quality in Sudan's agroecological zones, supporting sustainable agricultural practices and enhanced productivity. These findings can be directly applied to optimize okra production in Sudan, contributing to the country's agricultural sustainability.